Self-assessment of secondary school Islamic education teacher: validity and reliability of qualitative study - Masuwai, Azwani; Zulkifli, Hafizhah; Hamzah, Mohd Isa (International Journal of Evaluation and Research in Education (IJERE), 2025)
Issues concerning the validity of qualitative studies are frequently debated among scholars. Interview techniques often lack standardized procedures, which can affect reliability, and eliminating biases in interviews is challenging. Ensuring reliability and validity is crucial for establishing research credibility and high measurement reliability. This study was conducted to explore the reliability and validity of qualitative study of self-assessment concept among Islamic education teachers towards continuous professionalism development. The qualitative study was involved six participants selected based on the purposive sampling technique using a semi-structured interview. This study aimed to validate interview data through participant verification, ensure the validity of qualitative themes through expert validation, and enhance reliability via data triangulation. Multiple methods were employed to achieve these goals, including interview protocol verification, pre-field study, data triangulation, field notes, participant verification, expert validation, and agreement assessed using the Cohen Kappa Index, along with an extended study period. The findings indicated that the study met it is objectives for validity and reliability according to the recommended strategies and techniques. The use of various validation methods and attention to language barriers contributed to the study’s robustness and offers valuable guidance for future research.